Increases in core temperature counterbalance effects of haemoconcentration on blood viscosity during prolonged exercise in the heat - Buono, M. J.; Krippes, T.; Kolkhorst, F. W.; Williams, A. T.; Cabrales, P. (Experimental Physiology, 2016)
Previous studies have reported that blood viscosity is significantly increased following exercise. However, these studies measured both pre- and postexercise blood viscosity at 37°C even though core and blood temperatures would be expected to have increased during the exercise. Consequently, the effect of exercise-induced hyperthermia on mitigating change in blood viscosity may have been missed. The purpose of this study was to isolate the effects of exercise-induced haemoconcentration and hyperthermia and to determine their combined effects on blood viscosity. Nine subjects performed 2 h of moderate-intensity exercise in the heat (37°C, 40% relative humidity), which resulted in significant increases from pre-exercise values for rectal temperature (from 37.11 ± 0.35 to 38.76 ± 0.13°C), haemoconcentration (haematocrit increased from 43.6 ± 3.6 to 45.6 ± 3.5%) and dehydration (change in body weight = -3.6 ± 0.7%). Exercise-induced haemoconcentration significantly (P < 0.05) increased blood viscosity by 9% (from 3.97 to 4.33 cP at 300 s-1), whereas exercise-induced hyperthermia significantly decreased blood viscosity by 7% (from 3.97 to 3.69 cP at 300 s-1). When both factors were considered together, there was no overall change in blood viscosity (from 3.97 to 4.03 cP at 300 s-1). The effects of exercise-induced haemoconcentration, increased plasma viscosity and increased red blood cell aggregation, all of which increased blood viscosity, were counterbalanced by increased red blood cell deformability (e.g. red blood cell membrane shear elastic modulus and elongation index) caused by the hyperthermia. Thus, blood viscosity remained unchanged following prolonged moderate-intensity exercise in the heat.